Perfectionism and false memories: A signal detection analysis. (October 2016) - Ben-Artzi, Elisheva; Raveh, Michal
Abstract: The present study investigated true and false memory manifestations of adaptive and maladaptive perfectionism using the DRM (Deese-Roediger-McDermott) word lists paradigm. Ninety-seven college students were administered the DRM paradigm and completed the Almost Perfect Scale-Revised (Slaney, Rice, Mobley, Trippi, & Ashby, 2001). Signal detection analyses revealed that perfectionism strivings was associated with more accurate memory, whereas perfectionistic concerns was associated with higher levels of false memories and higher confidence ratings about the accuracy of these memories. Moreover, individuals high in perfectionistic concerns manifested a lower memory discriminative ability, suggesting poor working memory capacity. These findings corroborate previous studies suggesting a working memory involvement in false memories and call for further investigation into the cognitive and emotional processes underlying false memories. Highlights: False memory processes of adaptive and maladaptive perfectionism were examined. Measures: accuracy, sensitivity (d-prime), and confidence in the DRM paradigm Perfectionistic strivings was associated with high levels of accurate memory. Perfectionistic concerns was associated with high levels of false memories. Perfectionistic concerns manifested a lower memory discriminative ability.